The benefits of four weeks of melatonin treatment on circadian patterns in resistance-trained athletes - Leonardo-Mendonca, R. C.; Martinez-Nicolas, A.; de Teresa Galvan, C.; Ocana-Wilhelmi, J.; Rusanova, I.; Guerra-Hernandez, E.; Escames, G.; Acuna-Castroviejo, D. (Chronobiology International, 2015)
Exercise can induce circadian phase shifts depending on the duration, intensity and frequency. These modifications are of special meaning in athletes during training and competition. Melatonin, which is produced by the pineal gland in a circadian manner, behaves as an endogenous rhythms synchronizer, and it is used as a supplement to promote resynchronization of altered circadian rhythms. In this study, we tested the effect of melatonin administration on the circadian system in athletes. Two groups of athletes were treated with 100 mg day-1 of melatonin or placebo 30 min before bed for four weeks. Daily rhythm of salivary melatonin was measured before and after melatonin administration. Moreover, circadian variables, including wrist temperature (WT), motor activity and body position rhythmicity, were recorded during seven days before and seven days after melatonin or placebo treatment with the aid of specific sensors placed in the wrist and arm of each athlete. Before treatment, the athletes showed a phase-shift delay of the melatonin circadian rhythm, with an acrophase at 05:00?h. Exercise induced a phase advance of the melatonin rhythm, restoring its acrophase accordingly to the chronotype of the athletes. Melatonin, but not placebo treatment, changed daily waveforms of WT, activity and position. These changes included a one-hour phase advance in the WT rhythm before bedtime, with a longer nocturnal steady state and a smaller reduction when arising at morning than the placebo group. Melatonin, but not placebo, also reduced the nocturnal activity and the activity and position during lunch/nap time. Together, these data reflect the beneficial effect of melatonin to modulate the circadian components of the sleep-wake cycle, improving sleep efficiency.